Rosja w polityce Polski i Niemiec na przełomie pierwszej i drugiej dekady XXI wieku. Zakres zbieżności i różnicy stanowisk - Stolarczyk, Mieczysław (Studia Politicae Universitatis Silesiensis, 2017)
Abstract: Russia in the Polish and German policy at the beginning of the second decade of the 21st century. The range of convergences and discrepancies The aim of the present article is to outline the characteristics of Polish and German policy towards East, especially towards Russia. The author indicates the areas of common and different interests as well as objectives in the Polish and German policy towards East, particularly at the beginning of the second decade of the 21st century. In spite of observing fewer differences between Poland and Germany in their present policy towards Russia, the article aims to emphasize the discrepancies that still exist and are visible in the bilateral as well as multilateral relations. At the beginning of the second decade of the 21st century, the Polish and German positions towards Russia and post-soviet countries are noticeably more coherent than before. One of the main reasons is the modification of Polish Eastern policy by introducing pragmatic thinking (so-called positive realism), implemented at the end of 2007 by the Polish government run by the Civic Platform (PO) and Polish People’s Party (PSL). At the same time, the Angela’s Merkel government introduced more critical attitude towards Russia. Nonetheless, in spite of growing convergence of interests in Polish and German policy towards Russia, there have been significant discrepancies. The main differences have been related to the role of Russia in the Commonwealth of Independent States and in the European security system. Therefore, Poland and Germany have had different opinion on the role of Russia: should it be a partner or a threat? To what extend the process of Europeanization of Russia should be introduced? There is also a discrepancy between Poland and Germany related to the following question: which relations among the post-soviet countries should be prioritized, should it be relations with Ukraine or with Russia? Key words: eastern policy, common and different interests, multilateral relations